PKM Pelatihan Perancangan Prototype Internet of Things (IoT) untuk Smart Aquaculture - Jamiyanti, Eva; Ainur Rofiq, Mohammad; Wahyu Kurniawan, Danif (Transformative Service Journal, 2025)
Vocational High Schools Nurul Jadid (SMKNJ) as vocational education institutions have a strategic role in producing skilled human resources who are ready to face the challenges of industry 4.0. However, based on the results of observations and communication with SMK partners in coastal areas, it was found that students still have limited knowledge and skills in the application of Internet of Things (IoT) technology, especially in the context of relevant industrial worlds such as aquaculture. This is a major problem because the low understanding of technology makes SMK graduates less competitive and have minimal innovation in developing appropriate technology-based solutions. This community service activity was carried out in the form of intensive training for SMK students through the method of delivering materials, demonstrations, and direct practice workshops. The focus of the training was on creating a prototype of an IoT-based water quality monitoring system consisting of a microcontroller device (ESP32), temperature sensor, pH sensor, and cloud-based monitoring system (such as Blynk or Thingspeak). This solution not only provides conceptual understanding, but also practical skills that can be directly applied to the needs of industry and student projects. Based on the evaluation conducted using a pre-test, students' understanding of IoT concepts increased by 35%. This indicator of success was proven by feedback from participants, the successful training demonstrated their ability to independently build functional prototypes, and 95% of participants successfully assembled and programmed the basics. Thus, this activity is able to bridge the gap between industry needs and the skills of vocational school students and open up opportunities for local innovation in the field of smart aquaculture.